﻿The first adult mantis lacewing from Baltic amber, with an evaluation of the post-Cretaceous loss of morphological diversity of raptorial appendages in Mantispidae - Baranov, V; Pérez-de la Fuente, R; Engel, MS; Hammel, JU; Kiesmüller, C; Hörnig, MK; Pazinato, PG; Stahlecker, C; Haug, C; Haug, JT (Pensoft Publishers, 2022)
Mantis lacewings (Neuroptera: Mantispidae) are prominent and charismatic predatory representatives of Insecta. Nevertheless, representatives of the group are surprisingly scarce in Paleogene deposits after a relative abundance of specimens known from Cretaceous. Here we present Mantispa? damzenogedanica sp. nov., representing the first adult of Mantispidae described from Baltic amber and the only Eocene adult mantispid hitherto preserved in amber. The new fossil species is also among the earliest representatives of Mantispinae, certainly the oldest adult of this group described from amber. Additionally, we discuss the changes through time in the ecological morphospace within Mantispidae based on the morphological diversity (≈disparity) of the raptorial legs. Possible explanations for the post-Cretaceous decline in the morphological diversity of mantis lacewings are posited.